AKTIVITAS KOGNITIF DAN HUBUNGANNYA DENGAN BEBAN KOGNITIF SERTA KEMAMPUAN PENALARAN SISWA SMA PADA PEMBELAJARAN SIKLUS BIOGEOKIMIA MENGGUNAKAN WORKED EXAMPLES - Dahlan Noor Aziz, - (2020)
There are still many students who do not understand the step-by-step sequence of the processes and results of the processes that occur in the biogeochemical cycle images. The material of the biogeochemical cycle is said to be complex because during learning, students cannot directly observe the processes that occur both in the nitrogen and carbon cycles. This study used worked examples in learning biogeochemical cycle material. Worked examples show you the steps in getting a solution to a problem. This study aims to obtain information about cognitive activity and its relationship with cognitive load and reasoning abilities of high school students in learning biogeochemical cycles using a worked example. The research method used was a quasi experiment with a non-equivalent control group post-test only design. Participants taken in this study were 60 students from 2 class X MIPA academic year 2019/2020, in learning the biogeochemical cycle consisting of water, nitrogen, and carbon cycles in a high school in Bandung. The instruments used in this study were cognitive activity observation sheets, task complexity worksheets, a subjective rating scale questionnaire and two-tier reasoned questions. The cognitive activity of students who learned with the worked example was higher than that of the control class. Students' instrinsic cognitive load (ICL) and extaneous cognitive load (ECL) were categorized as low. Students' reasoning abilities are in the very high category. Cognitive activity contributed 70.7% to students' ability to receive and process information (MMI), which means it also contributed to the decrease in intrinsic cognitive load (ICL). Cognitive activity contributed 42.3% to students' mental effort (UM), which means there was also a contribution to extraneous cognitive load (ECL). Cognitive activity contributed 71.4% to students' reasoning abilities. The ability to receive and process information (MMI) contributed 47.3% to students' reasoning abilities. By using worked examples, students 'mental effort was lower and it did not contribute to building students' reasoning abilities. Keyword: cognitive activities, cognitive load, reasoning ability, biogeochemical cycle, worked examples